Evergreen management information system application project - Ortiga, Vito Antonio Liyao (Animo Repository, 2009)
Evergreen Stock brokerage firm has been operating with several errors. It’s operations contain too much of a human-error-possible paradigm but is too critical to entertain such flaw. Dealing with customers who plan to invest their money on a risky asset, stocks are meant to be carefully processed especially with sensitive information being used. The objective of the organization to become one of the leading stock brokerage firms in the Philippines by providing outstanding service towards its customers would be met once they capture an error free and hassle free transaction with the customers. The problems identified would also refine their operational processes and eventually get a robust information system for the management and user to use. An MIS tool used for the operations and management group is to be deployed in this traditional stock brokerage firm to achieve its goals. It will be developed from scratch based on the problems and other areas for improvement by the organization. This newly created MIS tool will be implemented and integrated together with the processes of the company in order for it to realize its full potential.